Pemantapan Tes Minat Bakat Di Kecamatan Medan Johor - Mawaddah Nasution (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2021)
Background: Many teenagers are confused about continuing their education to the next level. This is one of the reasons why this Community Service Activity was carried out. The number of teenagers who drop out of school and are still confused in determining their interests and talents in determining majors at school makes this service important for teenagers in the X neighbourhood of Suka Maju Village, Medan Johor District. The purpose of this Community Service is to help teenagers in the X Suka Maju Village, Medan Johor Subdistrict, in determining their level of intelligence directing their interests and talents in determining majors at school. This service collaborates with two partners, namely the head of the X neighbourhood of Suka Maju sub-district, Medan Johor sub-district and the Youth of the Assyafiiyah Mosque, with a total of 20 participants. Methods: Guide intelligence and talent interests, the relationship between intelligence and talent interests of adolescents, then carry out intelligence and talent interest tests to participants. Results: Teenagers can find out their level of intelligence and their interests and talents. Based on the findings that occurred in the field, almost all of the participants had never taken an intelligence test or an interest-aptitude test. They did not understand where their interests and talents were headed. Conclusion: Teenagers can find out their level of intelligence and the direction of their interests and talents. In addition, they can also determine the majors they will take at the next level (SMA) in school.